Effects of ankaferd blood stopper on soft tissue healing in warfarin treated rats - (:unkn) unknown (SUAMTHI PUBLICATIONS, 2016)
Ankaferd Blood Stopper (ABS) is a new promising local haemostatic agent. Although there are many studies showing its mechanism of haemostasis, histological and biochemical effects of ABS have not been studied in detail. Aim of this study was to evaluate the effects of this new generation local haemostatic agent on warfarin treated rats focusing on short term soft tissue healing. 12 systemically warfarin treated (warfarin group) and 12 none treated Wistar - Albino rats (control group) were selected for the trial. Rats in warfarin group were treated intraperitonally 0,1 mg/kg warfarin and rats in control group were given 1ml/kg saline 3 days earlier to surgical procedure and continued until sacrification. All rats had incisions on dorsal dermal tissue which was applied ABS or no haemostatic agent (NHAA) before suturing. Six of each group are sacrified on day 4, and the other 6 were sacrified on day 8. Prothrombin time (PT) in blood samples, collagen rate and histological evaluation in skin samples were determined. NHAA tissue samples' collagen rate decreased [p=0,008] but the collagen rate of ABS administrated tissue samples remained unchanged [p=0,257] from day 4 to 8 in the control group. Both ABS administrated tissue samples' [p=0,026] and NHAA tissue samples' [p=0,005] histologic total damage score values decreased from day 4 to 8 in warfarin group, but valuesof ABS administrated tissues were significantly higher than NHAA tissues in warfarin group at the eight day [p=0,006]. ABS seems to have a negative effect on short term soft tissue healing histologically under warfarin treatment.
Keywords: Warfarin; Ankaferd Blood Stopper; Collagen rate; Healing; MEDICINAL-PLANT EXTRACT; DENTAL EXTRACTIONS; EFFICACY; SKIN